SIGEMO: sistema de gestão de moldes - Marques, Rui (2005)
This paper presents the methods used for the development of a project that intends to contribute for the implementation of a logistic system of identification, management and flow control of materials (raw materials, products in assembly stage, tools and support machinery) for application in industrial environments. This work was the final project to obtain a degree in Electronics and Telecommunications Engineering. It was developed by its authors in collaboration with the “Programa Aveiro-Norte” and the “Grupo de Sistemas de Banda Larga” of the Electronics and Telecommunications Department of the University of Aveiro. The intent of this work was to enhance the identification, usage management and flow control of moulds for plastics in Simoldes Plásticos, an industrial unit of Simoldes, an industrial group responsible for injection of plastic products, especially for the automotive industry.